2014
DOI: 10.1016/j.fuel.2014.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Regenerable MgO-based sorbent for high temperature CO2 removal from syngas: 3. CO2 capture and sorbent enhanced water gas shift reaction

Abstract: Regenerable MgO-based sorbent, which was prepared and evaluated in the thermogravimetric analyzer (TGA) in part 1, was also evaluated in high-pressure packed-bed unit in CO 2 /N 2 /H 2 O mixture and simulated pre-combustion syngas environment. In CO 2 /N 2 /H 2 O environment, The CO 2 absorption capacity of the sorbent increases with increasing temperatures from 6.7% at 350°C to 9.5% 450°C. The sorbent is capable of achieving over 95% CO 2 capture and 40% conversion in the WGS reaction, which should be attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Figure 8b indicated that the CO 2 capture capacity of the SDS-assisted MgO sample eventually reaches a steady value of 0.5 mmol g −1 without further significant degradation, suggesting a great prospect of application in the sorption-enhanced hydrogen production processes [49,50].…”
Section: Cycling Stability Testsmentioning
confidence: 97%
“…Figure 8b indicated that the CO 2 capture capacity of the SDS-assisted MgO sample eventually reaches a steady value of 0.5 mmol g −1 without further significant degradation, suggesting a great prospect of application in the sorption-enhanced hydrogen production processes [49,50].…”
Section: Cycling Stability Testsmentioning
confidence: 97%
“…Abbasi et al studied regenerable MgO-based sorbent in CO 2 /N 2 / H 2 O environment, and the results showed that CO 2 sorption capacity of the sorbent increases with increasing temperatures from 6.7% at 350°C to 9.5% at 450°C. The MgO-based sorbent is capable of achieving over 95% CO 2 capture and 40% conversion in the water gas shift (WGS) reaction [67]. The regeneration reaction can be performed either at temperatures higher than the reaction temperatures or at lower pressures in a CO 2 -free atmosphere.…”
Section: Mgo Based Sorbentsmentioning
confidence: 99%
“…This code calculates the overall rate of reaction based on eq.9 and eq.10 and provides the source term (R j ) in the species conservation equations (T-6 and T-7). The model has been validated against TGA and packed bed experimental data in previous studies (Abbasi et al, 2013;Abbasi et al, 2014).…”
Section: Reaction Kineticsmentioning
confidence: 99%
“…The coupled method is based on the -Finite size domain Complete set of trial functions Method of Moment‖ (FCMOM) (Abbasi and Arastoopour, 2013). Another objective of this paper is to numerically assess the performance of the MgO-based sorbent 2014) in the proposed regenerative carbon dioxide capture and SEWGS process.For this purpose, we adopted a bench scale circulating fluidized bed reactor design from the National Energy Technology Laboratory (NETL) as our baseline (Breault et al, 2013;Clark et al, 2013). 5…”
Section: Introductionmentioning
confidence: 99%